Exuberant gingival lesion: a case of peripheral odontoma - Turella, Patricia Triches; Kovalski, Luan Nathiel Santana; Mariath, Adriela Azevedo de Souza; Martins, Manoela Domingues (Journal of Oral Diagnosis, 2020)
Odontomas are a benign lesion of odontogenic origin rarely found in deciduous dentition. We report herein a rare case of peripheral odontoma associated with an exuberant reactive gingival lesion. A two-year-old child was referred for evaluation due to asymptomatic gingival overgrowth. Intraoral examination revealed a firm consistency nodule in the superior anterior gingiva involving the left incisors. The radiographic image showed no alteration. The primary diagnostic hypothesis was a reactive proliferative process. An excisional biopsy was performed. Histopathological analysis revealed a peripheral complex odontoma associated with fibroepithelial hyperplasia. The patient completed treatment and was monitored with clinical and radiographic examinations for 16 months.